Hubungan antara kecenderungan perilaku berhati-hati dengan kecenderungan perilaku prokrastinasi pada mahasiswa peserta pendidikan karakter IAYP - Singgih Purwanto, Arundati Shinta, & FX. Wahyu Widiantoro (LPPM Universitas Proklamasi 45, 2017)
Procrastination is a kind of failure on self-regulation to accomplish a task based on voluntaryintention. Although he or she understands the consequence, this kind of behavior occursrepeatedly. This kind of harmful behavior frequently occurred among the IAYP (InternationalAward for Young People) participants. IAYP is a kind of character building program. The programrequires participants to accomplish three activities sport, skill, and community service onceper week during 24 weeks (either for bronze and silver level). This program trained participantto have internal motivation. This research is done in university proklamasi 45 yogyakarta.This research is a correlation research with subjects totaling 30 subjects. The subject is thestudents participating in IAYP. method of data collection is done with the scale, the scaleof procrastination and conscientiousness scale. This research had a normal distributionand has a linear correlation so that the data analysis is done by using the technique of KarlPearson Product Moment Correlation. The results of data analysis have shown that the valueof correlation coefficient or rxy = -0.693, p = 0.000 (p <0.01), meaning that there is a verysignificant relationship between behavioral variables to conscientiousness with variableprocrastination at the University of Proklamasi 45 YogyakartaKeywords: Procrastination, conscientiousness, character building